Influência do número e posicionamento de transferentes de escaneamento intra-oral na adaptação marginal de estruturas fresadas - Santos, Fábio Henrique de Paulo Costa (2022)
This in vitro study aimed to evaluate the influence of the number of intraoral scanning transfers and the positioning of their chamfer on marginal misfit of milled 3-element frameworks. A master model was prepared with 3 implants placed bilaterally, with 2 mini abutments under 2 transfers in each hemiarch. Two situations were then simulated: one side with transfers aligned to the buccal face, and on the other side, to the buccal and lingual faces. A full-arch scan was performed using an intraoral scanner (Virtuo Vivo, Straumann, Suíça). Secondly, the third abutment was installed followed by its transfer, with a chamfer following the previously defined pattern, totaling 3 transfers in each hemiarch; and thus, a new total intraoral scan was performed. The STL files (Standard Tessellation Language) were sent to the laboratory and 20 frameworks were planned and machined in cobalt-crome alloy (Co-cr), and located into 4 groups (n=5). Mesial and distal face of each prosthetic junction was evaluated by using a Scanning Electron Microscopy (SEM) following the Sheffield test, and horizontal and vertical misfits of each junction were quantified. Interproximal radiographs were performed with only one screw and qualitatively evaluated as clinically favorable or unfavorable. Results for marginal misfit and clinical practicability were analyzed using a statistical software (R Core Team, Foundation for Statistical Computing, Vienna, Áustria). Generalized linear models were applied for quantitative analysis. Fisher's exact test was applied for qualitative analysis. Both tests were performed assuming α=0.05. Better adaptation was observed in the 3 transfers group when compared to the group of only two. Marginal fit was better with misaligned chamfers than aligned. Clinical radiographic analysis corroborated microscopic results, showing the practicability of this type of clinical analysis resource. Factors inherent to the process, such as the number of transfers and the positioning of their chamfer, could influence on marginal misfit of milled CAD/CAM frameworks.